PENGARUH BEBAN KERJA DAN MOTIVASI KERJA TERHADAP TURNOVER INTENTION KARYAWAN RUMAH SAKIT PANTI WILASA CITARUM SEMARANG - Choirul Ibnu Setianto; Sudharto Prawoto Hadi; Agus Hermani Daryanto Seno (Jurnal Ilmu Administrasi Bisnis, 2021)
Abstract: The high turnover rate of employees in the company shows that employees demanded to leave the company. Based on the turnover data of the Panti Wilasa Citarum Hospital Semarang which shows fluctuations from 2017-2020. This study aims to determine the effect of workload and work motivation on employee turnover intention at Panti Wilasa Citarum Hospital Semarang. This type of research is explanatory research using cluster sampling method. The survey population includes all employees, with a sample of 85 respondents. SPSS 22.0 application is used to analyze the data. According to the research, it is found that workload and work motivation affect the turnover intention, and there is a simultaneous influence of workload and work motivation on turnover intention. Suggestions given on the workload aspect are to implement a target evaluation system on a regular basis, and provide training to increase insight and knowledge. In the aspect of work motivation, create a more comfortable work atmosphere and clarifies the work flow so that it can be organized and efficient in task completion. In the aspect of turnover intention, companies should provide promising career paths for employees in order to retain employees and make employees continue to develop. Keywords: Workload; Work Motivation; Turnover Intention